2014
DOI: 10.1136/sextrans-2013-051494
|View full text |Cite
|
Sign up to set email alerts
|

Sex on demand: geosocial networking phone apps and risk of sexually transmitted infections among a cross-sectional sample of men who have sex with men in Los Angeles county

Abstract: Background Geosocial networking applications (GSN apps) used to meet sexual partners have become increasingly popular with men who have sex with men (MSM) since 2009. The current study aimed to determine if self-identified HIV negative, MSM clinic attendees who used GSN apps have an increased incidence of sexually transmitted infections (STIs) compared to self-identified HIV negative, MSM attendees who met sexual partners via in-person venues such as bars or clubs or through MSM-specific hook-up websites. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
196
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(212 citation statements)
references
References 16 publications
11
196
1
4
Order By: Relevance
“…This study found that in a field-based sample of young, poor, primarily Black and Latino MSM and transgender women, social media access and frequent use were widely prevalent, which have important implications for outreach and engagement for HIV prevention and other health interventions. This is in contrast to prior studies of social media use and HIV risk behaviors by sexual minorities, which have largely been comprised of white and/or older MSM 19,32,33 with higher socioeconomic status 25 with few or no transgender individuals included. Additionally, we found that while majority of respondents reported using social media to meet sexual partners, the types of sites primarily used for this purpose varied (Table 2) and that different types of social media platform use (e.g., sexual networking versus more general sites) was associated with exchange sex, which has implications for developing tailored social media-based interventions targeting different risk groups within urban youth and young sexual minority populations.…”
Section: Discussioncontrasting
confidence: 46%
“…This study found that in a field-based sample of young, poor, primarily Black and Latino MSM and transgender women, social media access and frequent use were widely prevalent, which have important implications for outreach and engagement for HIV prevention and other health interventions. This is in contrast to prior studies of social media use and HIV risk behaviors by sexual minorities, which have largely been comprised of white and/or older MSM 19,32,33 with higher socioeconomic status 25 with few or no transgender individuals included. Additionally, we found that while majority of respondents reported using social media to meet sexual partners, the types of sites primarily used for this purpose varied (Table 2) and that different types of social media platform use (e.g., sexual networking versus more general sites) was associated with exchange sex, which has implications for developing tailored social media-based interventions targeting different risk groups within urban youth and young sexual minority populations.…”
Section: Discussioncontrasting
confidence: 46%
“…54 A cross-sectional study in Los Angeles found higher odds of gonococcal and chlamydial infection in MSM who used geosocial networking apps for meeting sex partners compared to MSM who met partners through in-person methods only. 55 Concerns regarding how online avenues might affect implementation of infection control were legitimised by a syphilis outbreak in 1999, where a cluster of syphilis cases in San Francisco was associated with meeting partners in an Internet chat room. 56 Public health efforts to conduct partner notification were hindered by the anonymity and privacy provided by the online chat room.…”
Section: Existing and Anticipated Challenges Of The Sti Epidemic In Msmmentioning
confidence: 99%
“…[4,5] Findings from other studies have been mixed as to whether STI diagnoses are related to either finding or searching for sexual partners online. [1][2][3][4]17, 20] A number of studies have reported on HIV testing history among gay men and tend to find that men who use apps are more likely to have been tested for HIV. [15,20] Studies in gay men in Australia, suggest that men who use a combination of mobile phone apps, internet websites and offline places to meet partners appear to be at increased risk of STIs or HIV compared with men who use a narrower range of online and offline methods.…”
Section: Principal Resultsmentioning
confidence: 99%
“…To date, most studies of meeting partners online have recruited specific populations and used convenience sampling strategies, such as targeting online users, gay venues or health care settings. [1][2][3] These settings are not representative and may result in an over-estimation of prevalence.…”
Section: Introductionmentioning
confidence: 99%